Blood pressure trend in children with chronic kidney disease in Nigeria, sub-saharan african region - Daberechi Kenneth Adiele; Ngozi Chinyelu Ojinnaka; Henrietta Uchenna Okafor; Josephat Maduabuchi Chinawa (Nigerian Journal of Medicine, 2023)
Background: Various mechanisms are involved in the development of hypertension in children with chronic kidney disease (CKD), some of which are due to the disease process, while some are due to the treatments employed in CKD. Aim: The aim of the study was to determine the trend of blood pressure in Nigerian children with CKD comparable with controls. Materials and Methods: A cross-sectional study assessing the blood pressure of children from 6 to 17 years with CKD and selected age- and sex-matched controls who were recruited consecutively at the Paediatric Nephrology Clinic and Children Outpatient Clinic of University of Nigeria Teaching Hospital. Data obtained were analyzed using the Statistical Package for the Social Sciences (SPSS) version 17. Results: The mean systolic blood pressure (SBP) was 126.08 ± 37.43 mmHg for subjects compared to 105.04 ± 14.33 mmHg for controls, whereas the mean diastolic blood pressure (DBP) was 78.96 ± 22.74 mmHg for subjects compared to 66.25 ± 10.66 mmHg for controls. The distribution of SBP and DBP across the CKD stages showed more severe hypertension (Stages I and II) prevalence in the later stages of CKD (Stages 4 and 5) (χy2 = 7.21, P = 0.01, respectively). The mean value of the mean arterial blood pressure (MAP) was 94.67 ± 26.98 mmHg for subjects compared to 79.18 ± 10.61 mmHg for controls. The increase in MAP across the stages of CKD was significant. Conclusion: This study shows a high prevalence of the severe forms of high blood pressure in this group of children with CKD in the subregion.